Práticas de transferência de aprendizagem situada em uma atividade interdisciplinar - Vanessa Sena Tomaz (2007)
The aim of this research is to comprehend WHAT, and mainly, HOW it is possible to learn when participating of the educational practice based in activities stated as interdisciplinary. The deepening of the theoretical elapsed parallelly to the effort of analytical comprehension of the empiric field constructed during the process of data collection within the principles of education ethnography (GREEN et al., 2001), used as logic of inquiry in the classroom. The data collection was carried out in a state public school of Pedro Leopoldo, Minas Gerais, Brasil, in groups of 7th and 8th grades of Elementary School. The peculiarity of the subject relationships within and out of the school and the educational practice features of this group have taken to the theoretical perspective use of the situated learning (LAVE, 1988; LAVE and WENGER, 1991). The inter-relation and, at the same time, the practice diversity which were observed have taken to the investigation of the relation between learning and transfer. The notion of activity (LEONT'EV, 1978) was adopted as a way of structuring the educational practice around the theme Water, and this allowed to capture the relation complexity among the several practices, describing the interdisciplinary education activity from the students' action perspective. The unity of central analysis is the students/teachers-in- action activity which structures educational practices developed by the students in interdisciplinary activities. To analyze the learning transfer which takes place in this complex structure, Greeno et al. (1993) language of attunements to constraints and affordances in interactive systems was adopted within the principles of Activity Theory. The learning process in the transfer practices is a attunements enlargement to the overall constraints and affordances which were perceived in activities or initial situations and considered relevant in the individual participation in another situation of activity. In these practices, the learning recontextualization, in which the knowledge is transformed in/to the practice and not conveyed from one situation to the other, as if it had come ready and concluded to the new situation. The transfer practices are structured in activities in which the individuals are in tune with the possibilities and invariable restrictions that perform the function of knowing generality in the activity. In the recontextualization process, new ideas, experiences and procedures emerged from the own practice are incorporated to these rudiments, distinguishing thus, the learning transfer situated in the activity. The presence of the transfer practices in the educational practice set which have the basis in the Water activity take the interdisciplinarity for granted.